THE IMPLICATION OF READING TECHNIQUE USE AND SELF-BELIEF TO READING COMPREHENSION IN UNIVERSITY - Rini Listyowati; Arisandi Setiyawan (Journal of English Educational Study (JEES), 2021)
Abstract: The research’s purpose is to perceive the implication of reading technique use and self-belief  to reading comprehension. This research is conducted to answer the problem do reading technique and self-belief fundamentally implication to college students’ reading comprehension. The problem was answered using alternative hypothesis stating reading technique and self-belief significantly implicate to college students’ reading comprehension. The reasearch used quantitative and research design is correlation. The subject of the reserach was 240 population students of English Education Department of Universitas Islam Madura Pamekasan. The sample was 150 students after being counted by Sloven theory. The sample was taken using simple random sampling with lottery media. The data was taken using questionnaire for reading technique which consisted of 30 points questions to know the frequency of reading technique use, questiannaire for self-belief which consisted of 9 questions for regulated learning and the answers scored using Likert Scale, the reading comprehension test consisted 40 questions were picked up from Longman Pre TOEFL reading test. The data were analyzed using regression formula to answer the reserach problem. Data analysis was counted using SPSS version 11.0. The result showed that reading technique and self-belief fundamentally implicate to the college students’ reading comprehension. It was authenticated by table of regression showing that the value of F is 14.339 (p<0.01). It meant that the data reject nul hypothesis and receive alternative hypothesis. It is substantiated reading technique and self-belief fundamentally to reading comprehension of students university.